2021
DOI: 10.3390/f12111537
|View full text |Cite
|
Sign up to set email alerts
|

Description of Intra-Annual Changes in Cambial Activity and Differentiation of Secondary Conductive Tissues of Aesculus hippocastanum Trees Affected by the Leaf Miner Cameraria ohridella

Abstract: Aesculus hippocastanum trees are commonly infested by the leaf miner Cameraria ohridella, whose larval activity causes the destruction of the leaf parenchyma and induces defoliation. Pest attacks result in, e.g., production of smaller fruits and tree re-flowering in autumn. Concerning pest influence on stem structure only scarce information of narrower annual growth rings of wood has been published. Therefore, we determined the effect of the presence of the leaf miner infestation on intra-annual cambial activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Extensive brown-yellow spots on leaves as well as rapid wilting and premature fall of leaves before the end of the growing season are the external symptoms of C. ohridella (horse-chestnut leaf miner) foraging [ 7 , 8 , 9 ]. As a result of infestation by many (5–7) generations of larvae of the pest, the tree is severely weakened, the photosynthetic efficiency declines, the intensity of flowering and the weight and size of fruit and seeds are reduced, and the size and vitality of developing seedlings decrease [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive brown-yellow spots on leaves as well as rapid wilting and premature fall of leaves before the end of the growing season are the external symptoms of C. ohridella (horse-chestnut leaf miner) foraging [ 7 , 8 , 9 ]. As a result of infestation by many (5–7) generations of larvae of the pest, the tree is severely weakened, the photosynthetic efficiency declines, the intensity of flowering and the weight and size of fruit and seeds are reduced, and the size and vitality of developing seedlings decrease [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transverse and longitudinal sections (8 µm thick) were prepared using a rotary microtome (Leica RM 2135, Germany) and stained with Alcian Blue-Safranin O solution, mounted in Euparal, and observed under a bright-field microscope with a polarization adapter. The cambial activity and processes of wood formation in ash and maple were analysed according to Myśkow et al . (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…The larvae mine the leaves, creating brown lesions that can eventually cover the entire leaf area and cause early defoliation. Although mature trees are rarely endangered by such defoliations, they can result in serious loss in radial growth and aesthetic values (Jagiełło et al, 2019;Myśkow et al, 2021), while mortality may occur in highly infested young trees (Salleo et al, 2003). Past studies in urban areas have shown that C. ohridella can be parasitized by insects (Girardoz, Quicke, et al, 2007a;Grabenweger et al, 2010;Volter & Kenis, 2013) and preyed by birds (Grabenweger, Kehrli, et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%